LEKSIKON ARKAIS SISTEM ORGANISASI SOSIAL MASYARAKAT DESA CENGAL KECAMATAN JAPARA KABUPATEN KUNINGAN (TELAAH ETNOLINGUISTIK) - Andriyana - (Bahasa Indonesia Prima, 2024)
This research examines the lexicon in the social organization system of the Cengal Village community, Japara Subdistrict, Kuningan Regency, which produces definitions and explanations of lexicons that have lexical meanings and those that do not have them The lexicons found are Kuwu, Juru Tulis, Ngabihi, Ketib, Raksa Bumi, Lulugu, Kemit, Ngalambang, Cap Gawe, Babau, Kaum, Paraji, Kuncen. The method used in this research is descriptive qualitative, with interviews and documentation supporting the search for meaning in each word.